Risk factors of severe hand, foot and mouth disease in Shantou, China: a case-control study - Chunhua Liu; Kaiyan Wang; Niyang Lin; Jianling Cai; Binglin Cui; Beiyan Wu (Journal of Infection in Developing Countries)
Introduction: In clinical perspectives, how to distinguish a small proportion of children at risk of developing neurological complications from a large number of children with mild symptoms still remains a challenge for primary care doctors.